2012
DOI: 10.1037/a0026718
|View full text |Cite
|
Sign up to set email alerts
|

Dissociating expectancy of shock and changes in skin conductance: An investigation of the Perruchet effect using an electrodermal paradigm.

Abstract: Is human Pavlovian conditioning driven by a unitary, propositional system (as claimed by Mitchell, De Houwer, & Lovibond, 2009) or by dual systems; one under conscious control, symbolic in nature, and requiring effort to deploy, and the other utilizing associative processes and automatic in its operation (McLaren, Green, & Mackintosh, 1994)? Past research has suggested that for electrodermal conditioning to occur in humans, conscious awareness of the contingencies is necessary to produce conditioned responding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(39 citation statements)
references
References 20 publications
1
36
2
Order By: Relevance
“…SCRs can be dissociated under certain conditions from cognitive contingency learning (Bechara et al, 1995;McAndrew, Jones, McLaren, & McLaren, 2012 Our conclusion runs counter the results of a number of studies that we mentioned in the introduction. We will discuss these studies in more detail here.…”
Section: Discussioncontrasting
confidence: 53%
“…SCRs can be dissociated under certain conditions from cognitive contingency learning (Bechara et al, 1995;McAndrew, Jones, McLaren, & McLaren, 2012 Our conclusion runs counter the results of a number of studies that we mentioned in the introduction. We will discuss these studies in more detail here.…”
Section: Discussioncontrasting
confidence: 53%
“…There was no significant difference between negative and positive runs in McAndrew et al (2012), and the data reported by Williams and Prokasy (1977) went descriptively in the wrong direction (note, however, that the procedure and notably the reinforcement rate, were different). The only result clearly in line with the Perruchet Length and Type of the Preceding Run Figure 5.…”
Section: Fear Conditioningcontrasting
confidence: 55%
“…In most studies, in keeping with Perruchet (1985), participants were instructed to rate during the intertrial interval (i.e., before the onset of E l) their expectancy that E2 will occur after the next E l (and not at the present time). Dismissing this measure amounts to considering that participants' expectancy of E2 after the next Elwouid change radically before and after the actual onset of E l. This hypothesis is not consistent with the fact that a between experiments comparison shows that ratings made before (e.g., Clark et al, 2001;Destrebecqz et al, 2010;Livesey & Costa, 2014;Perruchet, 1985;Weidemann et al, 2012) and after (McAndrew et al, 2012;Per ruchet et al, 2006) the onset of E l exhibit the same pattern. Moreover, at a more speculative level, the psychological processes that would motivate such a change in expectancy remain to be discovered.…”
Section: Are Anticipated Expectancy Ratings Valid?mentioning
confidence: 74%
“…In the current study, however, CS-US pairings did not have the same effects on US expectancy and SCRs, which argues against the idea that both measures being affected by one common underlying (cognitive) factor. Dissociations between both measures have been reported before (e.g., Bechara et al, 1995;McAndrew, Jones, McLaren, & McLaren, 2012) while cognitive and emotional components of fear conditioning sometimes converge (e.g., Costa, Bradley, & Lang, 2014;Dawson, Rissling, Schell, & Wilcox, 2007), questioning the classification into cognitive versus emotional measures. Thus, carefully designed experiments employing a multimodal approach will be invaluable to further refine and develop models of associative learning.…”
Section: Discussionmentioning
confidence: 99%